Assessing the Effects of Parthenolide on Inflammation, Bone Loss, and Glial Cells within a Collagen Antibody-Induced Arthritis Mouse Model - B. Williams; F. Lees; H. Tsangari; M. R. Hutchinson; E. Perilli; T. N. Crotti (Hindawi Limited, 2020)
Rheumatoid arthritis is characterised by a chronic inflammatory response resulting in destruction of the joint and significant pain. Although a range of treatments are available to control disease activity in RA, bone destruction and joint pain exist despite suppression of inflammation. This study is aimed at assessing the effects of parthenolide (PAR) on paw inflammation, bone destruction, and pain-like behaviour in a mild collagen antibody-induced arthritis (CAIA) mouse model. CAIA was induced in BALB/c mice and treated daily with 1 mg/kg or 4 mg/kg PAR. Clinical paw inflammation was scored daily, and mechanical hypersensitivity was assessed on alternate days. At end point, bone volume and swelling in the paws were assessed using micro-CT. Paw tissue sections were assessed for inflammation and pre-/osteoclast-like cells. The lumbar spinal cord and the periaqueductal grey (PAG) and rostral ventromedulla (RVM) regions of the brain were stained for glial fibrillary acidic protein (GFAP) and ionised calcium-binding adaptor molecule 1 (IBA1) to assess for glial reactivity. Paw scores increased in CAIA mice from days 5-10 and were reduced with 1 mg/kg and 4 mg/kg PAR on days 8-10. Osteoclast-like cells on the bone surface of the radiocarpal joint and within the soft tissue of the hind paw were significantly lower following PAR treatment (p<0.005). GFAP- and IBA1-positive cells in the PAG and RVM were significantly lower following treatment with 1 mg/kg (p<0.0001 and p=0.0004, respectively) and 4 mg/kg PAR (p<0.0001 and p=0.001, respectively). In the lumbar spinal cord, IBA1-positive cells were significantly lower in CAIA mice treated with 4 mg/kg PAR (p=0.001). The findings indicate a suppressive effect of both low- and moderate-dose PAR on paw inflammation, osteoclast presence, and glial cell reactivity in a mild CAIA mouse model.